Relevance of Lenin’s State and Revolution for the theoretical preparation of Bolsheviks to politically organize the new wave of creative revolutionary praxis of the working masses on the eve of the October revolution - Vratuša, Vera (Sociološki pregled, 2021)
This paper examines the relevance of Lenin’s theoretical work State and Revolution for the preparation of Bolsheviks to politically organize the new wave of creative revolutionary praxis of the working masses on the eve of the October 1917 Revolution in Russia, 150 years after the birth of the most influential Marxist of the XX century and inspiration of potential revolutionaries in the XXI century.The basic method used in this paper is the analysis of the main aspects of Lenin’s State and Revolution content and placement of this analysis within the context of the historically specific social and economic circumstances of the time in which Lenin finished writing it in the summer and autumn of 1917.The main finding of this analysis is that Lenin’s State and Revolution is the most relevant for the preparation of the Bolsheviks for the political organization of the new wave of revolutionary praxis of the working masses on the eve of the October 1917 revolution in Russia. In this work Lenin clarified both to himself and to his party comrades the revolutionary program of smashing the exploiting and oppressing bourgeois state as well as invention and organization of the new communal social form of semi-state withering away, without a standing army, police or bureaucracy, in which all literate citizens could take part in the administration of the common social problems
Keywords: state; revolution; dictatorship of the bourgeoisie; dictatorship of the proletariat; social democrats; anarchists; proletariat; introduction of revolutionary consciousness from without; force; transition from capitalism through socialism to communism